ENVIRONMENTAL ETHICS IN FRANK HERBERT’S THE GREEN BRAIN: DISCOURSE ANALYSIS - Ghofarho, Geofani Kevin; Tirmidi , Tirmidi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores how environmental ethics affect the balance of nature in Frank Herbert’s The Green Brain. Using suprasegmental analysis and intertextual analysis as methodological frameworks, this study investigates how narratives sensitize human consciousness towards nature, particularly through the concepts of Barrow’s (anthropocentric ethics, ecocentric ethics, biocentric ethics) and Carley and Christie’s (technocratic environmental ethics and managerial environmental ethics). The findings emphasize the novel’s depiction of ecological interdependence and its role in reshaping environmental consciousness through narrative structure. The research further reveals that literary narratives, particularly speculative fiction, serve as powerful vehicles for challenging dominant anthropocentric paradigms and fostering ecological awareness. By critically examining the symbolic and thematic dimensions of The Green Brain, this study underscores the importance of narrative in cultivating ethical responsibility toward nonhuman life forms. Literature is not merely reflective but also transformative, enabling readers to reconsider moral assumptions about nature. Ultimately, the novel serves as a critique of human environmental domination and a vision of sustainable coexistence grounded in mutual respect, balance, and ecological humility.